Indigenous Knowledge Governance Framework (IKGF) : A Holistic Model for Indigenous Knowledge Management - Narayanan, A/L N. Kulathu Ramaiyer; Tariq, Zaman; Yeo, Alvin Wee (2011)
The environmental and social conditions that indigenous communities interact with the external environment are characterized by a constantly increasing degree of complexity. The interaction between different cultures can be considered a multifaceted process of negotiation. It is well acknowledged that the use of Information and Communication Technologies (ICT) for indigenous cultural preservation and revitalization can lead to several challenges. In this context, Indigenous Knowledge (IK) represents a critical resource that needs to be focused towards specific processes and governance activities. The early efforts in knowledge management were on technologies to store, capture, and distribute knowledge, while the focus at present has shifted to make explicit, the tacit knowledge, but the development is more conceptual than practical. This study focuses on exploring the patterns of Indigenous Knowledge Management (IKM) and the supporting of a governance system of communities. Based on generic patterns of IKM, the goal of the research will be in developing an indigenous knowledge governance framework